Effects of Nicotine on Caenorhabditis elegans survival, reproduction, and gene expressions : Development of an Invertebrate Animal Model for Drugs of Abuse - Smith, Michael A. (East Carolina University, 2011)
Although much is known about the addictive effects of nicotine, the molecular mechanisms of nicotine-induced effects remain largely unclear. Specifically, little is known about the effects of nicotine on gene expression, including gene expression controlled by miRNAs. miRNAs may play a key role in regulating gene expression in response to nicotine exposure due to the fact that expression profiles of the miRNAs will be altered. These effects on gene expression may be associated with long-term use and the "addictive" behavior that is often exhibited with use of nicotine. Our goals are to explore the toxicity of nicotine on Caenorhabditis elegans (C. elegans), including survival, reproduction, and gene expression and to develop C. elegans as a model organism to assess the toxicity of various xenobiotics. We hypothesize that 1) Nicotine affects survival and reproduction of C. elegans; 2) The expression of several important genes, including the genes coding for the nicotinic acetylcholine receptor and for oxidative stress response, will be affected by nicotine exposure; and 3) The expression of miRNA genes will be changed and related to the selected protein coding gene expression. In survival trials, we tested a range of doses to obtain a 24- hour dose-response data. The 24-hour lethal dose-20 (LD20) in C. elegans corresponds to dose of ~3.16 ppm (19.5 uM) of nicotine. A reproduction study revealed that even at low nicotine exposure levels, egg-laying is affected. Using qRT-PCR, we found that the expression of several egg-laying and oxidative stress related genes were altered by nicotine, which may be regulated by miRNAs. We were able to analytically determine that the expression patterns of the selected protein coding genes were dose-related. In the miRNA assay, we analyzed the expression of four miRNAs (Cel-mir-70, Cel-mir-58, Cel-mir-790, Cel-mir-253.), which were selected by in-silico prediction of miRNAs that potentially target our protein-coding genes of interest. We found that individual miRNA expression profiles varied among the different concentrations, indicating that the nicotine concentration induces a differential miRNA expression. At 3.16 ppm, where the protein-coding genes are the most active, miRNAs are also up-regulated indicating there is a complex system of regulation based on more than one miRNA, many miRNAs may target the same gene. Therefore, we believe that miRNAs may play a key role in controlling protein-coding gene expression. The understanding of this relationship between the toxicant (nicotine) and its effects on miRNAs and their targeted genes will lead to a greater understanding of mechanisms of nicotine-related addiction.
Keywords: Biology; Chemistry, Biochemistry; Nicotine; Biochemistry; C. elegans; Caenorhabditis elegans; Nicotine addiction; Gene expression; RNA; Animal models in research